Regulated surface potential impacts bioelectrogenic activity, interfacial electron transfer and microbial dynamics in microbial fuel cell. (April 2020) - Modestra, J. Annie; Reddy, C. Nagendranatha; Krishna, K. Vamshi; Min, Booki; Mohan, S. Venkata
Abstract: Influence of surface anode potential on the performance of microbial fuel cell (MFC) was evaluated by opting positive and negative poised anode potentials (+100/-100 mV) on two MFCs, and studied at two phases (during potential (DP) and post potential (PP)) along with a third MFC operated as control (no applied anode potential). Variation in physico-chemical factors as well as biocatalytic metabolic behavior was analyzed in terms of electron transfer, power density, electro-kinetics and microbial community. Post potential operation at −100 mV depicted rapid electron transfer, higher redox catalytic currents (−0.44/0.42 mA) and voltage (653 ± 28 mV) in comparison to other experimental conditions. Disparity in electron carriers is noticed at both the phases with +100 mV (dominantly direct electron transfer)/-100 mV (cytochrome components) potential as well as control (non-specific and multiple carriers) which signify alteration in electron transfer mechanism aligned with change in surface potential. Microbial community analysis depicted the enrichment of exo-electrogenic bacteria belonging to phylum Proteobacteria (Gram negative bacteria) dominant at −100 mV, while Firmicutes (Gram positive bacteria) at +100 mV and a mixed bacterial population at control. Electrochemical investigations correlated with biological efficiency of MFC, which discerns a way to comprehend the underlying electron transfer process triggered in response to change in anode potential. Graphical abstract: Synoptic view of electron transfer from bacteria towards electrode and depiction of decreased activation energy (AE) at post potential (PP) phase with positive and negative poised potentials (+100 mV/-100 mV). Image 1 Highlights: MFC at −100 mV depicted higher bioelectrogenesis (653 ± 28 mV) than +100 mV. Post-potential phase illustrated less electron losses than during-potential phase at −100 mV. Dominantly, Proteobacteria were enriched at −100 mV and Firmicutes at +100 mV. Requirement of activation energy was less at post potential phase in −100 mV. Varied electron transfer modes viz. direct and mediated appeared for +100/-100 mV and Control.